Public procurement award criteria in the EU member states: a comparative study of the discretionary powers of contracting authorities - Bordalo Faustino, Paula (2017)
When choosing and applying the award criteria in the context of public procurement procedures, contracting authorities exercise their discretionary powers with a view to selecting the most economically advantageous tender. The importance of the use that contracting authorities make of their margin of discretion is directly related to the result of any public procurement procedure: the level of satisfaction of the contracting authorities’ needs provided by the works/supply/service contract concluded with the winning tenderer. Despite the tendency for public procurement regulation to focus on procedural rules (‘how to buy’), rather than the actual outcome of the procurement activity itself (‘what to buy’), there are substantive requirements derived from legislative sources, as well as soft law and jurisprudence, that somehow structure the contracting authorities’ decision making freedom. Although there is no standard unit that allows for the measurement of contracting authorities’ margin of discretion and its variation, this thesis aims to identify factors which contribute either to increase or to reduce the said margin. In other words, it is proposed to highlight the elements which determine the expansion or the limitation of the referred discretionary powers. The thesis concludes that despite the different national regulatory approaches to this topic under the common EU legal framework, the practice in the Member States covered by this thesis seems to indicate that contracting authorities exercise their discretionary powers in a (unknowingly) similar way.